2010
DOI: 10.1242/jeb.041368
|View full text |Cite
|
Sign up to set email alerts
|

Partition of aerobic and anaerobic swimming costs related to gait transitions in a labriform swimmer

Abstract: SUMMARYMembers of the family Embiotocidae exhibit a distinct gait transition from exclusively pectoral fin oscillation to combined pectoral and caudal fin propulsion with increasing swimming speed. The pectoral-caudal gait transition occurs at a threshold speed termed U p-c . The objective of this study was to partition aerobic and anaerobic swimming costs at speeds below and above the U p-c in the striped surfperch Embiotoca lateralis using swimming respirometry and video analysis to test the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 68 publications
2
92
2
Order By: Relevance
“…1. The cost function f in (4) shows that the fish is more high speed-averse for larger n, because it more rapidly grows for larger n. The cost function f in (4) is convex and increasing with respect to u; which is in good accordance with the conventional experimental results on swimming behavior of fishes (Brodersen et al 2008;Cucco et al 2012;Mori et al 2015;Roche et al 2013;Svendsen et al 2010;Yoshioka et al 2016a). The objective function is rewritten with (2) as…”
Section: Ordinary Differential Equationsupporting
confidence: 70%
“…1. The cost function f in (4) shows that the fish is more high speed-averse for larger n, because it more rapidly grows for larger n. The cost function f in (4) is convex and increasing with respect to u; which is in good accordance with the conventional experimental results on swimming behavior of fishes (Brodersen et al 2008;Cucco et al 2012;Mori et al 2015;Roche et al 2013;Svendsen et al 2010;Yoshioka et al 2016a). The objective function is rewritten with (2) as…”
Section: Ordinary Differential Equationsupporting
confidence: 70%
“…Korsmeyer et al, 2002;Svendsen et al, 2010). Oxygen consumption also continues to increase until U crit is reached (Dalziel et al, 2012a), as has been observed in striped surfperch, another labriform swimmer (Svendsen et al, 2010). Together, these observations suggest that U crit is a good measure of maximal aerobic swimming performance in sticklebacks.…”
Section: Measurement Of Maximum Prolonged Swimming Speed: U Critmentioning
confidence: 77%
“…In threespine sticklebacks, U crit is also tightly correlated with the gait transition from pectoral fin rowing to a combination of pectoral fin rowing and caudal bursts (Dalziel et al, 2012a), which is suggested to be a good measure of sustained swimming speed (e.g. Korsmeyer et al, 2002;Svendsen et al, 2010). Oxygen consumption also continues to increase until U crit is reached (Dalziel et al, 2012a), as has been observed in striped surfperch, another labriform swimmer (Svendsen et al, 2010).…”
Section: Measurement Of Maximum Prolonged Swimming Speed: U Critmentioning
confidence: 82%
“…The post-exercise recovery period or oxygen debt is directly related to the intensity of exercise (Svendsen et al, 2010). There are obvious advantages to reducing Tetanus stress (A) was significantly greater at 25°C test temperature than at 15°C regardless of acclimation treatment (significant differences between test temperatures are indicated by horizontal bars with different letters).…”
Section: Discussionmentioning
confidence: 99%